Impacts of In Ovo Feeding of DL-Methionine on Hatchability and Chick Weight - İsa Coşkun; Güray Erener; Ahmet Şahin; Ufuk Karadavut; Aydın Altop; Aylin Ağma Okur (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to determine the effect of in ovo DL-methionine injection into the fertile broiler eggs on hatchability and relative chick weight. In the trial, 132 fertile broiler eggs were obtained from a breeder flock (34-wk-old Ross 308 parent stock). Fertile eggs were randomly assigned to two experimental groups. Experimental groups were 1) Control 2) DL-methionine injected group with three replicates. Injections were carried out at the 16th day of incubation. At the end of the study, hatchability was 90.29%, and 84.74% in control and DL-methionine injected eggs respectively. Relative chick weights were 70.04% and 72.70% control and DL-methionine injected group respectively. At the end of the study, it determined that injection of DL-methionine increased 3.8% relative chick weight according to control. It suggested that DL-methionine may use as an in ovo feed additive for obtain heavier chick.